RNA-Binding Protein ZFP36L2 Downregulates Helios Expression and Suppresses the Function of Regulatory T Cells - Makita, Sohei; Takatori, Hiroaki; Iwata, Arifumi; Tanaka, Shigeru; Furuta, Shunsuke; Ikeda, Kei; Suto, Akira; Suzuki, Kotaro; Ramos, Silvia B. V.; Nakajima, Hiroshi (Frontiers in Immunology, 2020)
The zinc finger protein 36-like 2, ZFP36L2, is a member of a small family of RNA-binding proteins composed by ZFP36 (also known as tristetraprolin, TTP), ZFP36L1 and ZFP36L2 in humans, with corresponding murine orthologs. These proteins bind to adenine uridine-rich element (ARE) in the 3’untranslated region of target messenger RNA and stimulate target degradation. ZFP36 functions as an anti-inflammatory modulator in murine models of inflammatory diseases by down-regulating the production of inflammatory cytokines such as tumor necrosis factor-. However, how ZFP36L1 and ZFP36L2 alter the function of CD4+ T cells is not completely understood. We addressed this issue by searching for the target genes of ZFP36L2 by comprehensive transcriptome analysis. We observed that ZFP36L2 is highly expressed in naïve CD4+ T cells; however, when CD4+ T cells is stimulated with T cell receptor, ZFP36L2 expression is rapidly reduced in both humans and mice. Among CD4+ T cell populations, the expression levels of ZFP36L2 in regulatory T cells (Tregs) were lower than those in naïve or effector CD4+ T cells. RNA-sequence analysis revealed that the forced expression of ZFP36L2 decreased Ikzf2 (encoding Helios) expression in Foxp3+ Tregs and inhibited the ability of induced Tregs (iTregs). ZFP36L2 destabilized the 3’untranslated region of Ikzf2 mRNA, which contains AU-rich elements. These results indicate that ZFP36L2 reduces the expression of Ikzf2 and suppresses iTreg function, suggesting that the inhibition of ZFP36L2 in iTregs could be a therapeutic strategy for autoimmune diseases.